(untitled) (DAPesquisa, 2020)
The essay is based on classic and contemporary writers to present the historical and conceptual bases of essay writing. Concomitantly, it deals with the author’s experience in the site-specific construction of the urban intervention in art Darkness Awaits (conceived and presented in September 2018 in Lomé, Togo). In this way, the text presents and defends the relevance both of using the literary essay format for writing derived from academic research that discusses practice in art and of what is defined as an “essay methodology” for the production of works and knowledge in art.